2002
DOI: 10.1046/j.1365-8711.2002.04984.x
|View full text |Cite
|
Sign up to set email alerts
|

A Hubble Space Telescope lensing survey of X-ray-luminous galaxy clusters — II. A search for gravitationally lensed EROs⋆

Abstract: We present the results of a survey for extremely red objects (EROs) undertaken in the fields of 10 massive galaxy cluster lenses at z∼0.2, combining sensitive, high‐resolution Hubble Space Telescope imaging with deep, half‐arcsecond K‐band imaging from UKIRT. We detect 60 EROs with (R−K)≥5.3, of which 26 have (R−K)≥6.0 in a total image‐plane survey area of 49 arcmin2 down to K=20.6, including one multiply imaged ERO. We use detailed models of the cluster lenses to quantify the lens amplification and thus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
26
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 75 publications
(134 reference statements)
8
26
0
Order By: Relevance
“…The measured ellipticity of J1c is ǫ = 0.03 ± 0.01 (at PA=133 deg.) and its total magnitude (within a 6 ′′ -diameter aperture) is R 702 = 21.27 ± 0.03 (our best estimate of the Kband magnitude of J1c is K = 18.44 ± 0.10, giving a color of (R − K) ∼ 2.9, similar to that expected for a dwarf spheroid or early-type disk cluster member, Smith et al 2002). Using GIM-2D (Simard et al 2002) we model the 2-D light distribution in J1c and obtain a best fit model (χ 2 = 1.3) with a half-light radius of r hl = 0.40 ± 0.05 or ∼ 1.6 kpc and a bulge-to-disk ra-tio of 0.30 ± 0.05, suggesting the galaxy is an early-type disk (Sab).…”
Section: The True Nature Of J1csupporting
confidence: 62%
“…The measured ellipticity of J1c is ǫ = 0.03 ± 0.01 (at PA=133 deg.) and its total magnitude (within a 6 ′′ -diameter aperture) is R 702 = 21.27 ± 0.03 (our best estimate of the Kband magnitude of J1c is K = 18.44 ± 0.10, giving a color of (R − K) ∼ 2.9, similar to that expected for a dwarf spheroid or early-type disk cluster member, Smith et al 2002). Using GIM-2D (Simard et al 2002) we model the 2-D light distribution in J1c and obtain a best fit model (χ 2 = 1.3) with a half-light radius of r hl = 0.40 ± 0.05 or ∼ 1.6 kpc and a bulge-to-disk ra-tio of 0.30 ± 0.05, suggesting the galaxy is an early-type disk (Sab).…”
Section: The True Nature Of J1csupporting
confidence: 62%
“…ERO J003707 was first detected in HST † imaging of A 68 as part of our lensing survey of X-ray luminous galaxy clusters (Smith et al 2001a;S02a;Smith et al 2002b, in preparation -S02b). A 68 was observed with HST /WFPC2 for 7.5 ks through the F702W filter and 8.8 ks using UFTI on the 3.8m United Kingdom Infrared Telescope ‡ (UKIRT).…”
Section: Observationsmentioning
confidence: 99%
“…The importance of EROs to our understanding of galaxy formation and the intrinsic faintness of these systems (R > ∼ 23, K > ∼ 18) recently motivated us to search for EROs in the fields of massive gravitational lenses (Smith et al 2002a -S02a). In this letter, we present near-infrared spectroscopy of ERO J003707+0909.5, drawn from S02a's sample.…”
Section: Introductionmentioning
confidence: 99%
“…Cimatti et al 2002a), Moreover, their relatively large K-band fluxes suggested high stellar masses, comparable with local ellipticals, leading to the interpretation of EROs as already assembled elliptical galaxies and the redshift range z > 2 as their formation epoch. The correct prediction of such an early and efficient forma-tion of massive galaxies at high redshift is a well known challenge for models of galaxy formation based on the CDM cosmology: in fact early implementations predicted lower space densities of EROs than observed (e.g., Firth et al 2002;Smith et al 2002).…”
Section: Introductionmentioning
confidence: 99%